Cancer Caregiving in the United States Research, Practice, Policy - Talley, Ronda C.; McCorkle, Ruth.; Baile, Walter F.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Despite advances in detection and treatment, cancer remains a source of pain and distress to patients and of complex challenges to the loved ones caring for them. The trend toward shorter hospital stays in particular has increased the physical, psychological, and financial burden on caregivers, often leading to adverse effects on patients. Cancer Caregiving in the United States illuminates these complex concerns with authoritative detail. This wide-ranging volume provides a comprehensive survey of cancer-related issues, including those affecting the care triad (patients-family members- professionals) and quality of care as well as the numerous physical, emotional, and financial challenges that caregivers may need to confront. Sources of caregiver difficulty at each stage of the disease, from diagnosis to end of life, are explored. Each chapter analyzes its topic in terms of practice, research, education, and policy, providing a wealth of literature reviews, assessment and care models, interventions, and recommendations for future study and practice. Coverage includes: Caregiving issues for cancer patients with long-term, short-term, and intermittent needs. Family caregivers as members of the treatment team. The impact of health disparities on caregivers. Cancer care policy and advocacy. End-of-life issues for cancer caregivers. Legal, financial, and ethical issues.  Cancer Caregiving in the United States is a core reference for researchers, professionals/scientist-practitioners, and graduate students in such caregiving fields as clinical psychology, social work, nursing, public health and medicine, social policy, and educational policy.
1. Caring for a Loved One with Cancer: Professional and Family Issues.- Section I: Issues Affecting the Care Triad -- 2. Diagnostic Issues: Family Dynamics & Caring for an Individual with Cancer -- 3. The Emotional Responses of Family Caregivers: Living with the Cancer and Helping Families Cope -- 4. The Impact of Health Disparities on Cancer Caregivers -- 5. Education, Training, and Support Programs for Caregivers of Individuals with Cancer -- 6. What Professional Caregivers in Health Care Can Do: Family Caregivers as Members of the Treatment Team -- Section II: Issues in Providing Direct Care -- 7. Issues in Providing Developmentally Appropriate Caregiving for Cancer Patients with Short-term/Intermittent Care Needs -- 8. Issues in Caregiving for Cancer Patients with Long-term Care Needs -- 9. End-of-Life Issues for Caregivers of Individuals with Cancer -- 10. Advances in Cancer Care Impacting Familial Caregiving -- Section III: Cross-cutting Issues Impacting Caregivers and Caregiving -- 11. Faith-based Issues in Caring for a Loved One with Cancer -- 12. Economic Issues in Cancer Care -- 13. Legal Issues in Caregiving for Individuals with Cancer -- 14. Cancer Care Policy and Advocacy: National and State Initiatives -- 15. Ethical Issues in Caregiving for Individuals with Cancer -- Section IV: Conclusions -- 16. Caregiving and Cancer: Changed Lives and the Future of Cancer Care.
Keywords: Health psychology; Nursing; Social work; Medicine; Social policy; Educational policy; Education and state; Health Psychology; Nursing; Social Work; Medicine/Public Health, general; Social Policy; Educational Policy and Politics